Randomized Controlled Trials on Complementary and Traditional Medicine in the Korean Literature. (21st January 2015) - Kim, Chang-Kyu; Kim, Da-Hee; Lee, Myeong Soo; Kim, Jong-In; Wieland, L. Susan; Shin, Byung-Cheul
Abstract : Objective . This study aimed to identify all of the features of complementary and alternative (CAM) randomized controlled trials (RCTs) in the Korean literature and then introduce English-speaking researchers to the bibliometric and risk of bias characteristics of this literature. Methods . Eleven electronic databases and sixteen Korean journals were searched to August 2013 for RCTs of CAM therapies. Key study characteristics were extracted and risk of bias was assessed using the Cochrane Collaboration's tool for assessing risk of bias. Results . Three hundred and sixty publications met our inclusion criteria. Complementary and traditional medicine RCTs in the Korean literature emerged in the mid-1990s and increased in the mid-2000s. The most common CAM interventions include acupuncture (59.4%) and herbal medicine (8.3%). The largest proportion of trials evaluated CAM for musculoskeletal conditions (20.7%). Adequate methods of randomization were reported in 41.7% of the RCTs, whereas only 8.3% reported adequate allocation concealment. A low proportion of trials reported participant blinding (34.2%) and outcome assessor blinding (22.5%). Conclusions . Korean CAM RCTs are typically omitted from systematic reviews resulting in the potential for language bias. This study will enable these trials of diverse quality to be identified and assessed for inclusion in future systematic reviews on CAM interventions.